2020
DOI: 10.1186/s12935-020-01403-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological significance of SNHG20 in human cancers: a meta-analysis

Abstract: Background: It has been widely reported that the expression levels of SNHG20 are elevated in diverse types of cancers, indicating that SNHG20 may participate in cancer initiation and development. Besides, accumulating evidence reveals that SNHG20 overexpression is also connected with poor clinical outcomes among cancer patients. Herein, we carry out a systematic meta-analysis to further determine the prognostic and clinical significance of SNHG20 expression in various human cancers. Methods: Qualifying publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In agreement with our data, SNHG20 expression markedly increased in tumor tissues and promoted the malignant progression in laryngeal squamous cell carcinoma ( Li et al, 2019 ), epithelial ovarian cancer ( Wang et al, 2019 ), and osteosarcoma ( Zhang et al, 2018 ). Upregulated SNHG20 expression is capable of serving as an innovative predictive factor of inferior clinical outcomes in cancer patients ( Zhu H. et al, 2020 ). On the other hand, one limitation of our study is that our research regarding the 13 genes that make up our signature and predict survival is insufficient; further validation in clinical practice is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our data, SNHG20 expression markedly increased in tumor tissues and promoted the malignant progression in laryngeal squamous cell carcinoma ( Li et al, 2019 ), epithelial ovarian cancer ( Wang et al, 2019 ), and osteosarcoma ( Zhang et al, 2018 ). Upregulated SNHG20 expression is capable of serving as an innovative predictive factor of inferior clinical outcomes in cancer patients ( Zhu H. et al, 2020 ). On the other hand, one limitation of our study is that our research regarding the 13 genes that make up our signature and predict survival is insufficient; further validation in clinical practice is needed.…”
Section: Discussionmentioning
confidence: 99%
“… 25 SNHG20 expression was increased in multiple cancers, suggesting an effect of SNHG20 on cancer development and progression. 26 In HCC tissue samples, LINC00205 expression was significantly increased and LINC00205 enhanced the proliferation, migration and invasion of HCC cells. 27 AC092171.4 sponges miR-1271 and upregulate GRB2 to promote HCC development.…”
Section: Discussionmentioning
confidence: 94%
“…Due to the limited number of articles containing RFS of NPC, the present meta-analysis did not find any significant association between lncRNA expression and the RFS of patients with NPC. Multiple studies have identified lncRNAs, such as ZEB1-AS1, lncRNA ATB, SNHG12 and SNHG20, as potential prognostic markers for RFS in various tumors (15,(59)(60)(61). Furthermore, the neutrophil-to-lymphocyte ratio, O blood group, EBV DNA and serum LDH have been proposed as potential biomarkers for RFS in patients with NPC (62-65).…”
Section: Discussionmentioning
confidence: 99%